2010
DOI: 10.1002/ajh.21670
|View full text |Cite
|
Sign up to set email alerts
|

Pain as an emergent issue in thalassemia

Abstract: Thalassemia is a congenital blood disorder often requiring chronic blood transfusions and iron chelation therapy [1,2]. While advances in treatment have resulted in increased life expectancy [3], extended life spans have exposed previously unidentified issues, including bodily pain. The aim of this study was to examine the prevalence, severity, predictors, and effects of pain in 265 adults/adolescents and 103 children with thalassemia. Overall, 69% of adults/adolescents reported bodily pain on the SF-36v2 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…Pakbaz et al (2005) reported moderate pain in 21% of both transfusion-dependent (N = 29) and transfusion-independent (N = 19) thalassaemia patients (aged 14Á6 AE 7Á5 years), with severe pain in 14% of transfusion-dependent and 5% of transfusion-independent patients. An analysis of SF-36 Quality of Life data, collected as part of the Thalassaemia Longitudinal Cohort (TLC), revealed a significant relationship between increasing age and pain (Trachtenberg et al, 2010). This study also found a trend between low bone mass and bodily pain reports, but it did not reach significance (Trachtenberg et al, 2010).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Pakbaz et al (2005) reported moderate pain in 21% of both transfusion-dependent (N = 29) and transfusion-independent (N = 19) thalassaemia patients (aged 14Á6 AE 7Á5 years), with severe pain in 14% of transfusion-dependent and 5% of transfusion-independent patients. An analysis of SF-36 Quality of Life data, collected as part of the Thalassaemia Longitudinal Cohort (TLC), revealed a significant relationship between increasing age and pain (Trachtenberg et al, 2010). This study also found a trend between low bone mass and bodily pain reports, but it did not reach significance (Trachtenberg et al, 2010).…”
Section: Discussionmentioning
confidence: 75%
“…An analysis of SF-36 Quality of Life data, collected as part of the Thalassaemia Longitudinal Cohort (TLC), revealed a significant relationship between increasing age and pain (Trachtenberg et al, 2010). This study also found a trend between low bone mass and bodily pain reports, but it did not reach significance (Trachtenberg et al, 2010). An assessment of the relationship between bone and joint pain in 361 thalassaemia patients found no association between pain reports, bone mass and fractures (Vogiatzi et al, 2009).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Parents reported pain in 56% of children and that pain occurred fairly often in 11% [40]. Pain was localized to the back (24%), knees (15%), head/neck (10%), large bones (8%) and small bones/ribs (5%).…”
Section: Guidelines and Discussionmentioning
confidence: 99%
“…Pain was found to increase with age, diverging most sharply from U.S. age-matched normal values at age 35 years. Pain is also associated with increased anxiety and depression and with a decrease in quality of life observed in patients with thalassemia as they age [40]. …”
Section: Guidelines and Discussionmentioning
confidence: 99%